2021
DOI: 10.23846/wp0040
|View full text |Cite
|
Sign up to set email alerts
|

The policies that empower women: empirical evidence from India’s National Rural Livelihoods Project

Abstract: The International Initiative for Impact Evaluation (3ie) promotes evidence-informed equitable, inclusive and sustainable development. We support the generation and effective use of high-quality evidence to inform decision-making and improve the lives of people living in poverty in low-and middle-income countries. We provide guidance and support to produce, synthesise and quality assure evidence of what works, for whom, how, why and at what cost. 3ie working papers These papers cover a range of content. They ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the context of Indonesia, MSMEs led by women tend to be poorly structured with small-scale business forms. Studies have shown that women entrepreneurs tend to have fewer competencies and thus face various challenges to develop their businesses due to the cultural, social, and economic aspects of their operations (Hendratmi et al, 2022;Kochar et al, 2022). However, even when female entrepreneurs have the required competencies, growth outcomes tend to be unpredictable (Ladge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of Indonesia, MSMEs led by women tend to be poorly structured with small-scale business forms. Studies have shown that women entrepreneurs tend to have fewer competencies and thus face various challenges to develop their businesses due to the cultural, social, and economic aspects of their operations (Hendratmi et al, 2022;Kochar et al, 2022). However, even when female entrepreneurs have the required competencies, growth outcomes tend to be unpredictable (Ladge et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They are sometimes the decision makers in their household from small things to big things. It can be considered that women are always involved in making decisions in the household (Kochar et al, 2022). Women take a very important role in the process alongside their husbands.…”
Section: Introductionmentioning
confidence: 99%